DO the math, DON'T overpay. We make high quality, low-cost math resources a reality.

factor out a cos(x) to get:cosx*(tanx + 1)*(tanx + cotx)=cosx*(tan^2x + 1 + tanx + cotx)=cosx*(sec^2x + (sin^2x + cos^2x)/(sinx*cosx)) [1]= secx + cscx[1] since a/b + b/a = (a^2 + b^2)/(a*b) and tan^2x + 1 = sec^2x

factor out a cos(x) to get:

ReplyDeletecosx*(tanx + 1)*(tanx + cotx)

=cosx*(tan^2x + 1 + tanx + cotx)

=cosx*(sec^2x + (sin^2x + cos^2x)/(sinx*cosx)) [1]

= secx + cscx

[1] since a/b + b/a = (a^2 + b^2)/(a*b) and tan^2x + 1 = sec^2x